2010
DOI: 10.1143/jjap.49.04dd19
|View full text |Cite
|
Sign up to set email alerts
|

Physical Model for Reset State of Ta2O5/TiO2-Stacked Resistance Random Access Memory

Abstract: We investigated the conduction mechanism of a Ta2O5/TiO2-stacked resistance random access memory (ReRAM) device and found that its highly resistive state can be attributed to tunnel barriers induced in the filament, since single-electron tunneling phenomena was observed in the current–voltage characteristics at low temperatures and the resistance depended only slightly on temperature. We also found that the largest tunnel barrier, whose resistance is more than 1000 times larger than the second largest one, is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…It is clearly evident that all devices with thin insulators exhibit a logarithmic growth in the low-bias direct regime (observable only for sufficiently thin barrier), while a distinct transition from logarithmic growth to the linear decay is seen in the high-bias FN tunneling regime. As a result, one can concluded from FN plots and fitted theoretical results (Figures 4a,b) that the transport mechanism is due primarily to the quantum mechanical tunneling, instead of the defect-related conduction observed in conventional TiO 2 and Ta 2 O 5 films, 57 thanks to the extremely low defect density and surface roughness of our atomically flat ultrathin TiO 2 and Ta 2 O 5 converted from 2D TMD crystals.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…It is clearly evident that all devices with thin insulators exhibit a logarithmic growth in the low-bias direct regime (observable only for sufficiently thin barrier), while a distinct transition from logarithmic growth to the linear decay is seen in the high-bias FN tunneling regime. As a result, one can concluded from FN plots and fitted theoretical results (Figures 4a,b) that the transport mechanism is due primarily to the quantum mechanical tunneling, instead of the defect-related conduction observed in conventional TiO 2 and Ta 2 O 5 films, 57 thanks to the extremely low defect density and surface roughness of our atomically flat ultrathin TiO 2 and Ta 2 O 5 converted from 2D TMD crystals.…”
Section: ■ Results and Discussionmentioning
confidence: 66%
“…esistive random access memory (RRAM) has been reported as a competitive candidate for nextgeneration nonvolatile memory because of its high operation speed, low power consumption, simple device structure, and excellent scalability. 1,2) There are many resistive switching materials such as perovskite, 3) binary transition metal oxides, [4][5][6] carbon-based materials, 7) and organic polymers 8) being investigated. Among these materials, aluminum oxide (AlO x ) is proposed to be one of the most promising materials owing to its compatibility with conventional complementary-metal-oxide-semiconductor (CMOS) technology.…”
mentioning
confidence: 99%
“…The one consisting of metallic atoms is called conductive bridge RAM (CBRAM), and the other consisting of oxygen vacancies is called oxide-based RAM (OxRAM). [15][16][17][18] ReRAMs with a Hf-oxide dielectric layer have been studied extensively. [19][20][21][22] It is reported that most of the conductive filaments of ReRAM with the HfO 2 layer consist of oxygen vacancies, and the diffusion of oxygen vacancies (i.e., oxygen ions) occurs between the oxygen-rich and oxygen-poor regions upon voltage application.…”
Section: Introductionmentioning
confidence: 99%